One Health Perspective of Salmonella Serovars in South Africa Using Pooled Prevalence: Systematic Review and Meta-Analysis - Ramatla, Tsepo; Tawana, Mpho; Onyiche, ThankGod E.; Lekota, Kgaugelo E.; Thekisoe, Oriel (International Journal of Microbiology, 2022)
Salmonella is a bacterium that is commonly associated with food-borne infections and is regarded as one of the most important pathogens in public health. Salmonella serovars, particularly Typhimurium and Enteritidis, which are widely distributed globally, mainly result in outbreaks commonly linked to the consumption of animal products. This study is a systematic review and meta-analysis of studies reporting the prevalence of Salmonella serovars from one health perspective that included human, environmental, and animal samples in South Africa. PubMed, ScienceDirect, African Journals Online, and Scopus databases were used to conduct extensive searches of articles which were ultimately included or excluded following the Systematic Reviews and Meta-Analysis (PRISMA) guidelines. According to the data obtained in this review, the overall pooled prevalence estimates (PPE) of Salmonella serovars detection were 79.6%, 61.6%, 56.5%, and 43.2% for human, environment, animal, and environment/animal samples in South Africa, respectively. The majority of the studies (50%) used the polymerase chain reaction (PCR) technique for the detection of Salmonella serovars, followed by culture methods (26.7%), while 20% used serotyping. The PPE for nontyphoidal Salmonellae (NTS) was 65.6% and 34.4% for Salmonella Typhimurium and Salmonella Enteritidis, respectively. Our data further shows that 3 serovars, namely, Salmonella Typhimurium, Salmonella Enteriditis, and Salmonella Hadar, have been isolated from animals, humans, and the environment in South Africa. Our results highlight the ongoing spread of Salmonella spp. especially on animals which might end up infecting humans via direct contact with infected animals or eating infected animal products. This calls for deliberate “One Health” epidemiological studies in order to document information on the transmission between humans, animals, and the environment. This will ultimately result in the formulation of a consolidated salmonellosis control policy by the environmental, human, and veterinary health sectors.